El liderazgo transformacional de los gerentes del área metropolitana de Bucaramanga, una relación con el desempeño financiero (2013)
This study aims to determine the relationship of the leadership style of managers in the performance of companies in the Metropolitan Area of Bucaramanga - AMB (Colombia). This research was conducted based in Bass theory, using the validity survey titled Leadership Styles Questionnaire CELID, in a transversal, descriptive, exploratory and relational shtudy to 329 managers of AMBColombia. The results show that the manager of the Metropolitan Area of Bucaramanga has a preference for transformational leadership style, which shows a positive relationship with financial results.